Preobrazba ljubezni v zreli in pozni ustvarjalnosti Franca Ksaverja Meška - Avsenik Nabergoj, Irena (Slavia Centralis, 2025)
The present paper offers a thematological and semiotic analysis of the transformation of love in the poetic, narrative, and drama works of Franc Ksaver Meško (1874-1964), presenting love as the emotional, ethical, and spiritual core of his poetics. Meško’s priestly vocation, which had led him to consciously renounce romantic love, profoundly shapes his literary imagination - from youthful idealization to renunciation, contemplation, and mystical devotion. Prominent motifs include romantic, maternal, patriotic, and saintly love, while his depictions of fallen women are imbued with empathy, inner conflict, and a didactic function. Meško’s writing draws on biblical patterns, Tolstoy’s The Power of Darkness, Cankar’s social sensitivity, and Andersen’s symbolism. This paper illuminates his portrayal of love as a symbolic language oscillating between longing and renunciation, emotional authenticity and transcendent silence, revealing the tension between the bodily and the spiritual, between silence and speech, and between suffering and sanctity.
Keywords: duhovniški poklic in odpoved; fallen maidens; intertextuality; ljubezen kot žrtev; love as sacrifice; medbesedilnost; Meško, Franc Ksaver; padla dekleta; priesthood and renunciation